The Role of the Husband in Coping with Breast Cancer: How to Adapt to Emotional Challenges and Effectively Support the Wife - Kmichou, Halima; Klaina, Mekki; Ziani, Aicha (International Journal of Education, Culture, and Society, 2025)
Studying a woman's cancer diagnosis and its impact on marital relationships, along with the husband's role in supporting her, is crucial due to the widespread prevalence of this disease and the significant marital challenges it can cause, sometimes even leading to divorce. This research analyzes the psychological and social challenges couples face, examines the illness's impact on their relationship, and highlights the husband's supportive role during this difficult period. Notably, the husband is also vulnerable to emotional setbacks, highlighting his need for psychological support as well. This research includes a systematic review of previous studies on couples facing breast cancer, employing both descriptive and analytical methodologies. The findings indicate that religious values and personal beliefs can serve as therapeutic tools, helping couples cope with the emotional trauma casused by the illness. Additionally, shared medical decision-making, mutual emotional support, and joint coping strategies play a vital role in reducing emotional distress. The study further concludes that the husband's emotional support is a key factor in enhancing the wife's quality of life. These findings underscore the need for counseling programs for spouses to help them navigate the challenges associated with the disease effectively.